2022
DOI: 10.3389/fcell.2022.906530
|View full text |Cite
|
Sign up to set email alerts
|

The TRiCky Business of Protein Folding in Health and Disease

Abstract: Maintenance of the cellular proteome or proteostasis is an essential process that when deregulated leads to diseases like neurological disorders and cancer. Central to proteostasis are the molecular chaperones that fold proteins into functional 3-dimensional (3D) shapes and prevent protein aggregation. Chaperonins, a family of chaperones found in all lineages of organisms, are efficient machines that fold proteins within central cavities. The eukaryotic Chaperonin Containing TCP1 (CCT), also known as Tailless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 205 publications
(277 reference statements)
0
22
0
Order By: Relevance
“…Biotinylated CT20p did not bind to CCT2 150-407, while a second truncated version of recombinant CCT2 protein that retained more of the equatorial domain, (CCT2 17-526) did bind to biotinylated CT20p, Figures 8B, C . These results suggest that CT20p likely binds to a region on CCT2 (and possibly other subunits) that contains most of the equatorial domain of the subunit, potentially blocking sites for intra- and inter-ring contacts between subunits as well as portions of the nucleotide or ATP binding site, including catalytic aspartate residues ( 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Biotinylated CT20p did not bind to CCT2 150-407, while a second truncated version of recombinant CCT2 protein that retained more of the equatorial domain, (CCT2 17-526) did bind to biotinylated CT20p, Figures 8B, C . These results suggest that CT20p likely binds to a region on CCT2 (and possibly other subunits) that contains most of the equatorial domain of the subunit, potentially blocking sites for intra- and inter-ring contacts between subunits as well as portions of the nucleotide or ATP binding site, including catalytic aspartate residues ( 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using CT20-NPs, we showed that IMR-32 neuroblastoma cells are sensitive to the peptide’s cytotoxic effects. While CT20p has not yet been tested in clinical trials, we anticipate that cytoprotective pro-tumor effects associated with HSP90 inhibitors would not transpire given that reductions in CCT levels do not induce a heat shock response ( 17 ) and cct genes have fewer heat shock elements for binding heat shock transcription factors (HSF1 and HSF2) than comparable HSPs ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations